Práticas pedagógicas para alunos com transtorno do espectro autista: processos inclusivos no contexto escolar - Lopes, Carla Markus (2022)
This work is part of the research line of Pedagogical Management in Educational Contexts, of the Postgraduate Program in Public Policies and Educational Management at the Federal University of Santa Maria/RS (Universidade Federal de Santa Maria/RS). The study focuses on building strategies that qualify the reception, as well as favoring the process of adaptation and interaction of students with Autism Spectrum Disorder in the school context, based on the teachers' contributions which are involved in this process. The main theorists who contribute to the reflections of this research on public policies and educational management in the school environment are: Dourado (2007), Libâneo (2002) (2015) regarding the inclusive perspective of the school are: Baptista (2009), Freitas (2008), Mantoan (2008), Canabarro (2018), Pavão (2019), Pereira (2014), Oliveira (2017), (Pereira 2016). When approaching reflections on teaching in the emerging context of inclusion, we searched for studies by Bolzan (2016) (2002) (2009) (2019), Garcia (2005), Schmidt (2014), Pereira (2016), Oliveira (2020). The investigation begins from the challenges faced as manager and teacher of Public School. It was used, as methodology, the qualitative narrative approach of sociocultural nature, which has as data collection instruments narrative spaces in formats of meetings with pre-school and 1st grade teachers of an Elementary School of the Municipal Department of Education. Subsequently, the narrative contributions of the research collaborators were guidelines for the interpretation of the findings, as well as for the elaboration of a guiding document with propositions that contribute to the goals of the educators regarding the reception processes and initial interactions of these students in pre-school education and 1st grade of Elementary School. The context in which the study was developed concerns an Elementary School in the Municipal Department of Education of Santa Maria.